Assessment of machining with uncoated and coated end mills and determining surface topography using 2D fast Fourier transform. (1st January 2012) - Durakbasa, M.N.; Demircioglu, P.; Bogrekci, I.; Bas, G.; Gunay, A.
This study focuses on establishing a methodology for the surface roughness characterisation of uncoated and nano multilayer coated tools deposited by physical vapor deposition (PVD) managing an evaluation process after comparison of both experimental measurements utilising the stylus profilometer and the digital microscope, and also image processing technique, fast Fourier transform (FFT). The results showed that the surface roughness of coated cutting tool stayed reasonably constant while those of uncoated cutting tool changed drastically. Cutting edge of uncoated cutting tool was worn out during machining (about 2 mm width and 0.5 mm depth) while that of coated cutting tool remained its original shape almost the same after 25 min. The results from image processing agreed with those from roughness measurement technique. It can be concluded that micro/nano scale measurement techniques combined with image processing technique establish an improved evaluation methodology for the surface of the high precision milling tools.